-4(2w-1)+6w=6+2(2w-6)

Simple and best practice solution for -4(2w-1)+6w=6+2(2w-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2w-1)+6w=6+2(2w-6) equation:


Simplifying
-4(2w + -1) + 6w = 6 + 2(2w + -6)

Reorder the terms:
-4(-1 + 2w) + 6w = 6 + 2(2w + -6)
(-1 * -4 + 2w * -4) + 6w = 6 + 2(2w + -6)
(4 + -8w) + 6w = 6 + 2(2w + -6)

Combine like terms: -8w + 6w = -2w
4 + -2w = 6 + 2(2w + -6)

Reorder the terms:
4 + -2w = 6 + 2(-6 + 2w)
4 + -2w = 6 + (-6 * 2 + 2w * 2)
4 + -2w = 6 + (-12 + 4w)

Combine like terms: 6 + -12 = -6
4 + -2w = -6 + 4w

Solving
4 + -2w = -6 + 4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-4w' to each side of the equation.
4 + -2w + -4w = -6 + 4w + -4w

Combine like terms: -2w + -4w = -6w
4 + -6w = -6 + 4w + -4w

Combine like terms: 4w + -4w = 0
4 + -6w = -6 + 0
4 + -6w = -6

Add '-4' to each side of the equation.
4 + -4 + -6w = -6 + -4

Combine like terms: 4 + -4 = 0
0 + -6w = -6 + -4
-6w = -6 + -4

Combine like terms: -6 + -4 = -10
-6w = -10

Divide each side by '-6'.
w = 1.666666667

Simplifying
w = 1.666666667

See similar equations:

| 6(x+3)=(8n+9) | | 2.1+0.9+1.2= | | 0.81x+13100=0.54x+20700 | | 12m=-204 | | -4x-8y+68=180 | | 3x+4(2x-13)=80 | | (1-u)(2u+5)=0 | | 4w-2-2w=-20 | | -4=-12+x | | 22=3n+40 | | 4x+4(2x-13)=80 | | -1=-5a+4a | | y=2(20)+40 | | [h+-8]=[h+10] | | 16=-6b+2b | | M=3n+40 | | 6-9x=7x-9x-15 | | x^2-2x-30=5 | | 2x*2+6x-71=0 | | A(7)+b=c(7)+d | | -2m+4=100 | | -13=-9-a | | 24x^3-12x^2=0 | | -7=-3k+4k | | 1/2(-10)+10=y | | 25-3x-2(5-x)=0 | | 7*p-(3*p+4)=-2(2*p-1)+10 | | 5b+5a-2b+a= | | x(x+2)=139 | | -18+x=-6 | | -92-x=103-14x | | 4x^10-9x^10= |

Equations solver categories